Orality, literacy, memory in the ancient Greek and Roman world - Mackay, E. Anne. (Mnemosyne, Supplements, 2008)
The volume represents the seventh in the series on Orality and Literacy in the Ancient Greek and Roman Worlds. It comprises a collection of essays on the significance and working of memory in ancient texts and visual documentation, from contexts both oral (or oral-derived) and literate. The authors discuss a variety of interpretations of 'memory' in Homeric epic, lyric poetry, tragedy, historical inscriptions, oratory, and philosophy, as well as in the replication of ancient artworks, and in Greek vase inscriptions. They present therefore a wide-ranging analysis of memory as a fundamental faculty underlying the production and reception of texts and material documentation in a society that gradually moved from an essentially oral to an essentially literate culture.